Pengaruh Ketersediaan Kuliner UMKM pada Berbagai Platform Online terhadap Keputusan Pembelian Konsumen - Hasna Risa Bilqis Aulia; Muh. Naufal Mahfuuzhoh; Dhio Gusty Miranda; Bintang Taufik Bisri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The development of online platforms has transformed consumer purchasing behavior, including in the culinary MSME sector. Product availability across multiple online platforms has become an important factor influencing consumers’ purchasing decisions. This study aims to analyze the effect of the availability of culinary MSME products on various online platforms on consumer purchasing decisions. This research employs a quantitative approach using an explanatory research method. Data were collected through questionnaires distributed to consumers who had purchased culinary MSME products via more than one online platform. Data analysis techniques included validity testing, reliability testing, simple linear regression analysis, and hypothesis testing (t-test). The results indicate that the availability of culinary MSME products on various online platforms has a positive and significant effect on consumer purchasing decisions. These findings suggest that the easier culinary MSME products are to find, access, and consistently available across multiple online platforms, the higher the likelihood of consumers making purchasing decisions. This study is expected to contribute theoretically to digital marketing literature and provide practical insights for culinary MSMEs in developing effective multi-platform marketing strategies.